2021
DOI: 10.1096/fj.202101061r
|View full text |Cite
|
Sign up to set email alerts
|

The double‐edged sword effect of HDAC6 in Aβ toxicities

Abstract: Alzheimer's disease (AD) is the most common form of dementia and is marked with cognitive impairment, cell loss, and reduction of life expectancy. Pathologically, senile plaque, beta-amyloid (Aβ) aggregates, and neurofibrillary tangle, tau aggregates, are the hallmark of the disease. Although genetics studies provide a causative link between the disease and Aβ accumulation, the interaction between Aβ and tau and its contribution to the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…[12] Moreover, HDAC6 engages in interactions with tau protein to promote tau hyperphosphorylation, which results in neurofibrillary tangles (NFTs) formation. [16,17] Therapeutics potential of HDAC6 inhibitors (HDAC6is) is gaining more interest after pharmacological treatments of some selective HDAC6is in AD models show reduction of tau levels, improvement in axonal transport and restoration of learning and memory, and anti-inflammatory activity. [4,[18][19][20] However the underlying role of HDAC6 in AD needs further investigation at cellular levels for the advancement of potential drug molecules.…”
Section: Introductionmentioning
confidence: 99%
“…[12] Moreover, HDAC6 engages in interactions with tau protein to promote tau hyperphosphorylation, which results in neurofibrillary tangles (NFTs) formation. [16,17] Therapeutics potential of HDAC6 inhibitors (HDAC6is) is gaining more interest after pharmacological treatments of some selective HDAC6is in AD models show reduction of tau levels, improvement in axonal transport and restoration of learning and memory, and anti-inflammatory activity. [4,[18][19][20] However the underlying role of HDAC6 in AD needs further investigation at cellular levels for the advancement of potential drug molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have found increased HDAC6 in the brain of AD patients, leading to decreased levels of acetylated α -tubulin, destabilized microtubules of neurons, and eventually causing neuronal dysfunction 15 , 16 , 17 . In addition, HDAC6 elevates the tau protein phosphorylation and results in the A β -induced neuropathological change 18 , 19 . Accordingly, HDAC6 is emerging as a novel therapeutic target for AD treatment.…”
Section: Introductionmentioning
confidence: 99%